Psicoeducación y su aporte terapéutico en la reinserción social de un paciente - Lucas Garcia, Keyla Maria (2019)
The present case study has as its theme: “psychoeducation and its therapeutic contribution in the social reintegration of a patient, precisely with the aim of knowing the therapeutic contribution that psychoeducation gives in the social reintegration of an addict to society and in turn the diagnostic evaluation strategies and psychotherapeutic intervention focused mainly on cognitive behavioral and systemic psychotherapeutic models. The person participating and the main beneficiary of this research work turned out to be a patient treated in the CETAD Shelter House "Alma de Guerrero" of the Parish San Juan, and in turn their relatives or environment, who were ready to collaborate with the therapist and participate in the different stages of the therapeutic process. For the diagnostic assessment of the case, additional observation sheets, medical records, clinical interviews, tests were used to evaluate the indices of anxiety and underlying depression as well as to assess the affinity for alcohol and other drugs, after which the therapeutic scheme was planned with which he formulated a therapeutic scheme with a focus on cognitive-behavioral techniques, aimed at improving the emotional-emotional area, as well as in the patient's social relationships, which produced significant and favorable changes for his recovery process